Eighteen years' experience with tumor treating fields in the treatment of newly diagnosed glioblastoma - Vymazal, Josef; Kazda, Tomas; Novak, Tomas; Slanina, Petr; Sroubek, Jan; Klener, Jan; Hrbac, Tomas; Syrucek, Martin; Rulseh, Aaron M (Frontiers in oncology, 2022)
INTRODUCTION: The prognosis of glioblastoma remains unfavorable. TTFields utilize low intensity electric fields (frequency 150-300 kHz) that disrupt cellular processes critical for cancer cell viability and tumor progression. TTFields are delivered via transducer arrays placed on the patients' scalp. Methods: Between the years 2004 and 2022, 55 patients (20 female), aged 21.9-77.8 years (mean age 47.3±11.8 years; median 47.6 years) were treated with TTFields for newly-diagnosed GBM, and compared to 54 control patients (20 females), aged 27.0-76.7 years (mean age 51.4±12.2 years; median 51.7 years) (p=0.08). All patients underwent gross total or partial resection of GBM. One patient had biopsy only. When available, MGMT promoter methylation status and IDH mutation was detected. RESULTS: Patients on TTFields therapy demonstrated improvements in PFS and OS relative to controls (hazard ratio: 0.64, p=0.031; and 0.61, p=0.028 respectively). TTFields average time on therapy was 74.8% (median 82%): median PFS of these patients was 19.75 months. Seven patients with TTFields usage ≤60% (23-60%, mean 46.3%, median 53%) had a median PFS of 7.95 months (p=0.0356). Control patients with no TTFields exposure had a median PFS of 12.45 months. Median OS of TTF patients was 31.67 months compared to 24.80 months for controls. DISCUSSION: This is the most extensive study on newly-diagnosed GBM patients treated with TTFields, covering a period of 18 years at a single center and presenting not only data from clinical trials but also a group of 36 patients treated with TTFields as a part of routine clinical practice.